Long-term conservation agriculture with optimum nitrogen fertilization improves soil phosphorus availability - Nusrat Jahan Mumu; Sunjana Akter; Afsana Mimi Eiti Mony; Jannatul Ferdous; Nushaiba Atiq Taima; Most. Khatiza Khatun; Md. Mofizur Rahman Jahangir (PLoS ONE, 2025)
Understanding the interactive effects of conservation agriculture (CA) and nitrogen (N) fertilization on soil phosphorus (P) dynamics is critical for sustainable nutrient management. However, information on the dynamics and availability of P pools under the combination of long-term CA practices with N fertilization is limited. This study aimed to evaluate the long-term impacts of CA and different N rates on labile, moderately labile, and non-labile P fractions in a wheat (Triticum aestivum)-mungbean (Vigna radiata)-rice (Oryza sativa L) rotation after the 36th consecutive crop. The field experiment was conducted in a split-split plot design with two tillage systems (conventional tillage, CT; strip tillage, ST), two residue levels (lower residue, LR (15 cm); higher residue, HR (30 cm)), and six nitrogen (N) rates (N0, N60, N80, N100, N120, N140 representing 0%, 60%, 80%,100%, 120% and 140%, respectively of the recommended dose). The ST-HR significantly enhanced labile-P availability. Soluble-P, and NaHCO3-Po (organic) increased by 4% and 35% under ST compared to CT, and by 259% and 26% under HR compared to LR, respectively. While HR enhanced most soil P fractions, higher N rates (>N100) tended to decrease labile-Pi (inorganic) fractions by up to 45% suggesting a potential decline in plant-available P. The NaHCO3-Pi was higher in HR coupled with lower N rate (≤N100). Optimum N rate under CA aided in raising the NaHCO3-Po fractions. Moderately labile-P fractions were higher in ST-HR with increased N rate (>N100). Acid-P increased by 38% under ST, with complex interactions observed across treatments. Acid-P was consistently higher in ST-HR coupled with lower N rate (≤N100) while residual-P was higher in ST-LR coupled with same N rate. The interactions among tillage, residue, and N were significant for most P pools highlighting the synergistic effects of CA and N management. Overall, ST-HR-N100 was found to optimize P availability and minimize non-labile P buildup, offering a balanced P dynamics for improved soil fertility and sustainable crop production.